Authenticity and the cultural politics of work : new forms of informal control - Fleming, P. (Peter), 1972- (Oxford : Oxford University Press, 2009)
The 'personal' was once something to be put to one side in the work place: a 'professional manner' entailed the suppression of private life & feelings. Now many corporations encourage their employees to simply be themselves. This book investigates the increasing popularity of personal authenticity in corporate ideology & practice.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Organizational sociology; Psychology, Industrial; Personnel management